PEMEROLEHAN BAHASA ANAK PADA USIA PRASEKOLAH DI TAMAN KANAK-KANAK DESA SEMAYAP KABUPATEN KOTABARU - Sri Juniati; Tia Eka Safitri (CENDEKIA: JURNAL ILMIAH PENDIDIKAN, 2023)
This study aims to describe language acquisition, namely syntax acquisition, semantic acquisition and phonological acquisition in preschool-age children in Semayap Village Kindergarten, Kotabaru District. And describe the factors in the acquisition of the first language in children. The method used in this research is a qualitative research method. Qualitative research by analyzing and presenting data qualitatively through the steps of collecting, processing, analyzing and presenting data using observation and interview techniques. The results of the study showed that language acquisition at preschool age from the three stages of language acquisition which included syntax acquisition, there were 9 students who were very good and 9 students who were sufficient. For the acquisition of semantic students who were very good, there were 9 students and those who were quite good were 9 students. As for the acquisition of phonology, there were 10 students who were very good and those who were sufficient were 8 students. Factors that greatly influence the process of acquiring a child's first language are social background and hereditary factors. Keywords: children's language acquisition, preschool age